Combined modality treatment with “dexamethasone, methotrexate, ifosfamide, l-asparaginase, and etoposide” chemotherapy and involved field radiotherapy for early stage natural Killer/T cell lymphoma with local tumor invasiveness: A single-institution study from India - Vineet G Gupta; Ajay Gogia; Lalit Kumar; Atul Sharma; Sameer Bakhshi; Mehar C Sharma; Saumyaranjan Mallick; Ahitagni Biswas; Prashant Mehta; Sanjay Thulkar; Ranjit K Sahoo; Rakesh Kumar (Indian Journal of Medical and Paediatric Oncology)
Context: Patients with early stage extranodal natural killer/T-cell lymphoma, nasal type (ES-NKTCL) and local tumor invasiveness (LTI) show poor treatment outcomes with standard approaches. Dexamethasone, methotrexate, ifosfamide, L-asparaginase, and etoposide (SMILE) is an intensive, highly active protocol mainly studied in advanced/recurrent disease. No prior study has utilized this protocol in high-risk ES-NKTCL. Methods: Between 2011 and 2016, all patients with ES-NKTCL with LTI at presentation were uniformly treated at our institute with a combination of SMILE chemotherapy for 5–6 cycles, and involved-field radiotherapy (IFRT). Records of these patients were retrospectively reviewed. Results: Sixteen patients were identified, 69% stage IE and 31% stage IIE. The majority of patients had B-symptoms (75%), paranasal sinus (PNS) invasion (81%), facial skin invasion (56%), palatal perforation (69%), or orbital extension (56%). 12/16 had B-symptoms, and 6/16 had elevated lactate dehydrogenase. All patients received the entire planned 5–6 cycles. IFRT was delivered after a mean 4 cycles. Complete remission was achieved in 13/15 (87%) patients. At a median follow up of 18.5 months, 1-year progression-free survival and overall survival was 84% and 94%, respectively. Grade 3–4 toxicity was seen in 81%, most commonly neutropenia (75%), anemia (44%), and thromobocytopenia (31%). Six patients required dose adjustments (predominantly in the first 1 or 2 cycles). No treatment-related mortality was noted. Conclusion: SMILE with RT is a toxic but tolerable protocol for ES-NKTCL with LTI with high efficacy. Prospective studies are warranted.